2010
DOI: 10.1051/parasite/2010172143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency of bird-baited traps for sampling potential West Nile Fever mosquito vectors (Diptera: Culicidae) in Senegal

Abstract: Summary:The efficiency of bird-baited traps and collection heights for sampling potential West Nile mosquito vectors was studied during the 2006 rainy season (between September 27 and November 26) in Barkedji area situated in the sahelian area of Senegal (West Africa). Each night, two traps were set on the ground-level and two on the canopy-level (~ 3 m) each containing either a chicken or a pigeon, the traps being rotated the following nights. A total of 1,030 mosquitoes were collected using 66 traps-nights. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…In the Ferlo region of Senegal, 175 km south-east from Ross Bethio, Cx. neavei was also found more abundant in the tree canopy than on the ground, using both pigeon- and chicken-baited traps [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Ferlo region of Senegal, 175 km south-east from Ross Bethio, Cx. neavei was also found more abundant in the tree canopy than on the ground, using both pigeon- and chicken-baited traps [9]. …”
Section: Discussionmentioning
confidence: 99%
“…naevei, Mymomia spp., Mymomia hispida, M. lacustris, M. splendens, Aedomya africana [5], A. vexans and Mansonia uniformis [9]. All these species have a nocturnal feeding behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquito were collected monthly in villages and biweekly in ponds. In 2013, ponds were sampled biweekly with the traps listed above as well as bird-baited traps [20]. In November 2013, 3 ponds and 1 village were sampled once in Thiargny (50 km from Barkedji) following suspicion of an arbovirus outbreak.…”
Section: Methodsmentioning
confidence: 99%
“…Sharing these motifs of virulence mostly with MBFVs, NKVFs and CxFV than with AeFV showed that BAGV could be more closely related to MBFVs transmitted by Culex mosquitoes and could explain frequent BAGV isolations mainly from mosquitoes of Culex genus and its capacity to infect vertebrates such as wild birds [ 1 , 4 , 5 , 9 , 10 ]. In addition, The West African BAGV isolates characterized in our study were mainly isolated from Culex poicilipes and Culex neavei mosquitoes which have been reported as potential vectors for flaviviruses such as WNV [ 63 ]. Culex neavei was also found as a competent vector able to transmit flaviviruses such as USUV and WNV [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%